CHANGE IN AMINO ACID COMPOSITION OF BLOOD PLASMA IN CRITICALLY ILL PATIENTS - Elena Vladimirovna Alekseeva (Современная наука и инновации)
The studies of patients in critical condition showed a change in the amino acid composition of the blood. Aminogram determined by high-performance liquid chromatography - mass spectrometry, the results were processed by classical statistical analysis. Found that the greatest prognostic significance have levels in plasma citrulline and glutamic acid.